A Decade of Progress in Gene Targeted Therapeutic Strategies in Duchenne Muscular Dystrophy: A Systematic Review - Chung Liang, Lam; Sulaiman, Nadiah; Yazid, Muhammad Dain (Frontiers in Bioengineering and Biotechnology, 2022)
As one of the most severe forms of muscle dystrophy, Duchenne Muscular Dystrophy (DMD) results in progressive muscle wasting, ultimately resulting in premature death due to cardiomyopathy. In the many years of research, the solution to DMD remains palliative. Although numerous research including clinical trials have provided promising results, approved drugs, even, the therapeutic window is still minimal with much shortcomings to be addressed. Logically, to combat DMD that arose from a single genetic mutation with gene therapy made sense. However, gene-based strategies as a treatment option is no stranger to drawbacks and limitations such as the size of the dystrophin gene and possibilities of vectors to elicit immune responses. In this systematic review, we aim to provide a comprehensive compilation on gene-based therapeutic strategies and critically evaluate the approaches in relative to its efficacy, feasibility whilst addressing their current limitations. With the keywords “DMD AND Gene OR Genetic AND Therapy OR Treatment”, we reviewed papers published in Science Direct, PubMed, and ProQuest over the past decade (2012-2021).